Impacto do processamento de transcritos por Spliced Leader trans-splicing no repertório proteico de Schistosoma mansoni - Jéssica Silqueira Hickson Rios (2016)
The Spliced Leader trans-splicing (SLTS) is an insertion mechanism of 5' exon (Spliced Leader or SL) of specific RNAs (SL RNA) in mRNAs receptor molecules. The relevance of SLTS was attributed to mechanisms of post-transcriptional regulation, for changes in stability of mRNA molecules, to improve translation and to increase the diversity of the protein repertoire. The participation of SLTS in these processes has been suggested in various organisms, including Schistosoma mansoni. However, the impact of processing of the RNAs by SLTS on the whole parasite protein set is not known. By developing programs in Perl and Python languages, to parse data from sequencing of transcripts processed for SLTS, this work allowed the description of different forms of SLTS performance in protein-coding transcripts in S. mansoni and produced the conception of frequent situations and contingencies in this process. The results show that there is a higher incidence of SLTS in trans-splicing sites in non-translatable regions (5' UTR). Qualitatively, it was possible to observe that transcripts processed by SLTS can produce different proteins from those produced by native transcripts since the insertion of the SL can change the reading frame of the transcripts by ribosomes. Most transcripts that have more than one point of SL alternative entrance are liable to produce smaller peptides, without observed a standard size of peptides generated, however, most of them have changed the reading frame and do not carry alternative methionine for initiation of translation. Thus, small peptides can be produced without being functional and the synthesis of some proteins may be being lost. The majority of the proteins generated from transcripts without changes in reading frame lose large portions or complete sequences of functional domains, which reinforces the idea that the SLTS may hinder or prevent the activity of the processed protein. The data show the diversity of roles in the mechanism of SLTS that impact directly in the regulation of gene expression and consequently in proteins of the S. mansoni.